Effect of carbon chain length on the hydrolysis and transport characteristics of alkyl gallates in rat intestine. Issue 21 (29th September 2021) - Wang, Xinmiao; Chen, Kefan; Zhang, Xiumin; Hu, Yuanyuan; Wang, Zixu; Yin, Fawen; Liu, Xiaoyang; Zhang, Jianghua; Qin, Lei; Zhou, Dayong
Abstract : Phenolipids such as alkyl gallates (A-GAs) have been approved by food industry as non-toxic antioxidant additives. Abstract : Phenolipids such as alkyl gallates (A-GAs) have been approved by food industry as non-toxic antioxidant additives. However, their digestion and absorption mechanisms in the intestine have not yet been clarified. In this research, the hydrolysis and transport characteristics of A-GAs with fatty alcohols of various chain lengths (C1:0, C2:0, C3:0, C4:0, C8:0, C12:0 and C16:0) were estimated by the everted-rat-gut-sac model (ERGSM) for the first time. High-performance liquid chromatography measurements proved that measurable peaks corresponding to methyl gallate (G-C1:0), ethyl gallate (G-C2:0), propyl gallate (G-C3:0) and butyl gallate (G-C4:0) were discovered in the serosal fluids, which showed the short-chain alkyl gallates can cross the membrane in the form of esters. Besides, all A-GAs were hydrolyzed to GA in the mucosal solution, which contributed evidently to the transport of GA across the membrane of the small intestine. Meanwhile, the hydrolysis rate of A-GAs and transport rate of GA initially increased and then decreased with the chain length, exhibiting a maximum for octyl gallate (G-C8:0). In general, all A-GAs have the behavior of sustained-release. In consequence, the production of A-GAs should be an effective method to extend action time and further increases biological activities of GA.